Diamidophosphite–oxazolines with a pyridine core in Pd-catalyzed asymmetric reactions. Issue 24 (31st December 2016) - Gavrilov, Konstantin N.; Zheglov, Sergey V.; Novikov, Ivan M.; Lugovsky, Victor V.; Zimarev, Vladislav S.; Mikhel, Igor S.
Graphical abstract: Abstract: We have designed and synthesized a small library of readily available P, N, N -diamidophosphite–oxazoline ligands containing 1, 3, 2-diazaphospholidine rings and a pyridine moiety. The use of these ligands provides up to 96% ee in Pd-catalyzed asymmetric allylations of ( E )-1, 3-diphenylallyl acetate; up to 80% ee in the Pd-catalyzed asymmetric alkylation of cinnamyl acetate with ethyl 2-oxocyclohexane-1-carboxylate and up to 94% ee in the Pd-catalyzed desymmetrization of N, N ′-ditosyl- meso -cyclopent-4-ene-1, 3-diol biscarbamate. The influence of the structural modules, such as the nature of the phosphorus containing ring or pyridine substituent as well as of the addition of zinc(II) 5, 10, 15, 20-tetraphenylporphyrin on the catalytic activity and enantioselectivity is discussed. Abstract : (2 R, 5S)-2-[((4 S, 5 S )-2, 5-Diphenyl-4, 5-dihydrooxazol-4-yl)methoxy]-3-phenyl-1, 3-diaza-2-phosphabicyclo[3.3.0]octane: C27 H28 N3 O2 P Ee = 100% [ α ]D 25 = −157.7 ( c 1.0, THF) Source of chirality: ( S )-Glutamic acid and (1 S, 2 S )-2-amino-1-phenylpropane-1, 3-diol Absolute configuration: ( SC, RP, SC, SC ) Abstract : (2 R, 5 S )-2-[((4 S, 5 S )-5-Phenyl-2-(pyridin-2-yl)-4, 5-dihydrooxazol-4-yl)methoxy]-3-phenyl-1, 3-diaza-2-phosphabicyclo[3.3.0]octane: C26 H27 N4 O2 P Ee = 100% [ α ]D 25 = −151.1 ( c 1.0, THF) Source of chirality: ( S )-Glutamic acid and (1 S, 2 S )-2-amino-1-phenylpropane-1, 3-diol Absolute configuration: ( SC, RP, SC, SC ) Abstract : (2 R, 5 S )-2-[((4 S, 5 S )-5-Phenyl-2-(pyridin-3-yl)-4, 5-dihydrooxazol-4-yl)methoxy]-3-phenyl-1, 3-diaza-2-phosphabicyclo[3.3.0]octane: C26 H27 N4 O2 P Ee = 100% [ α ]D 25 = −164.5 ( c 1.0, THF) Source of chirality: ( S )-Glutamic acid and (1 S, 2 S )-2-amino-1-phenylpropane-1, 3-diol Absolute configuration: ( SC, RP, SC, SC ) Abstract : (2 R, 5 S )-2-[((4 S, 5 S )-5-Phenyl-2-(pyridin-4-yl)-4, 5-dihydrooxazol-4-yl)methoxy]-3-phenyl-1, 3-diaza-2-phosphabicyclo[3.3.0]octane: C26 H27 N4 O2 P Ee = 100% [ α ]D 25 = −124.1 ( c 1.0, THF) Source of chirality: ( S )-Glutamic acid and (1 S, 2 S )-2-amino-1-phenylpropane-1, 3-diol Absolute configuration: ( SC, RP, SC, SC ) Abstract : 2-[((4 S, 5 S )-5-Phenyl-2-(pyridin-3-yl)-4, 5-dihydrooxazol-4-yl)methoxy]-1, 3-diphenyl-1, 3, 2-diazaphospholidine: C29 H27 N4 O2 P Ee = 100% [ α ]D 25 = −2.8 ( c 1.0, THF) Source of chirality: (1 S, 2 S )-2-Amino-1-phenylpropane-1, 3-diol Absolute configuration: ( SC, SC )